The introduction and current status of the multidimensional model of pain neurobiology - Casey, Kenneth L. (Frontiers in Pain Research, 2023)
Conceptual models are useful, as they guide our actions related to whatever is represented by the model; this includes research revealing the limitations of these actions and the potential for their improvement. These statements apply to many aspects of life and to pain as a challenge for clinical practice and neurobiology. In the first half of the 20th century, our conceptual model of pain was based on evidence supporting the proposition that pain emerged from activity within a very limited set of central nervous system structures located within the cerebral cortex and its oligosynaptic connections with the thalamus. This CNS activity was associated with the activation of physiologically distinct somatovisceral afferent fibers. Nearly all aspects of the pain experience were thought to arise from changes in that CNS activity. There was no widely-accepted reason to consider an alternative model. However, neurophysiological, neuroanatomical, behavioral, and clinical evidence emerging in the late-20th century prompted a reconsideration of the model of pain neurobiology. Based on this new evidence and the limitations of the prevailing model, pain could be reasonably conceived as a multidimensional experience arising from the activation of physiologically and anatomically distinct but interacting CNS structures each separately mediating sensory discriminative, affective, and cognitive aspects of pain. This historical review describes the intellectual climate when this multidimensional model was proposed, the dispositions for resisting or accepting it, and concludes with a comment on the current status of the model as a fusion of distributed activations that create a unified perception of pain.